2022
DOI: 10.1007/s10660-022-09566-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to blockchain adoption for supply chain finance: the case of Indian SMEs

Abstract: Small and medium enterprises (SMEs) in India are suffering from the long-standing challenges related to asymmetric information, high transaction costs, SMEs’ opacity and limited access to credit. Blockchain technology, which is still in its infancy in terms of adoption in India, can facilitate SMEs to counter these challenges. Fuelled by this motivation, the study aims to investigate the significant barriers to blockchain adoption in supply chain finance practices by Indian SMEs. Using fuzzy-analytic hierarchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Among these, the technological obstacles showed the highest degree of importance. The third group of studies exclusively relied on ordinary fuzzy formats [38,39,44,52,80]. However, to handle uncertainty and to help experts and decision-makers, it would be necessary to extend such fuzzy approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, the technological obstacles showed the highest degree of importance. The third group of studies exclusively relied on ordinary fuzzy formats [38,39,44,52,80]. However, to handle uncertainty and to help experts and decision-makers, it would be necessary to extend such fuzzy approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, security and technology obstacles, which included scalability, showed the highest degree of importance. Kaur et al [52] utilized AHP and fuzzy DEMATEL, finding technological, organizational, security, knowledge, external, and financial barriers. Among these, technological barriers accounted for the most serious challenges while scalability barriers fell under the technological dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While discussing the barriers and challenges of blockchain adoption for supply chain finance in SME, Kaur et al [ 86 ] have identified technological, organizational, security, knowledge, external and financial barriers. Among these technological barriers, tech infrastructure, lack of automation and standardization, etc., are the most significant.…”
Section: Thematic Analysismentioning
confidence: 99%
“…And a conceptual framework is drawn to show the significance of I4.0 Singh et al ( 2022 ) The primary clients for the study are from industries and suppliers, which are the sustainable medium. The external pressures are created by society, the community, consumers, and the government Kaur et al ( 2022 ) This study indicates the technological barriers in the blockchain adoption process Chauhan et al ( 2022 ) The authors discussed technologies like machine learning and internet of things as beneficial for the CE. Several barriers were identified in the study.…”
Section: Literature Reviewmentioning
confidence: 99%